Diversity‐Oriented Synthesis of Drug‐Like Macrocyclic Scaffolds Using an Orthogonal Organo‐ and Metal Catalysis Strategy1. (26th September 2014) - Grossmann, André; Bartlett, Sean; Janecek, Matej; Hodgkinson, James T.; Spring, David R.
Abstract Small‐molecule modulators of biological targets play a crucial role in biology and medicine. In this context, diversity‐oriented synthesis (DOS) provides strategies toward generating small molecules with a broad range of unique scaffolds, and hence three‐dimensionality, to target a broad area of biological space. In this study, an organocatalysis‐derived DOS library of macrocycles was synthesized by exploiting the pluripotency of aldehydes. The orthogonal combination of multiple diversity‐generating organocatalytic steps with alkene metathesis enabled the synthesis of 51 distinct macrocyclic structures bearing 48 unique scaffolds in only two to four steps without the need for protecting groups. Furthermore, merging organocatalysis and alkene metathesis in a one‐pot protocol facilitated the synthesis of drug‐like macrocycles with natural‐product‐like levels of shape diversity in a single step.